Covid19 Pandemic: Management and Global Response - Haeril Amir; Sudarman Sudarman; Akbar Asfar; Andi Surahman Batara (Universitas Airlangga, 2020)
Introduction: 2019-nCoV as the term for the new coronavirus that causes outbreaks of pneumonia in Wuhan City, central China by the World Health Organization (WHO), on June 28, 2020, to confirm as many as 9,843,073 cases globally, Therefore, efforts to be made to prevent the spread of this virus must be done immediately and very urgently. The purpose of literature is to discuss the global response to Covid19 and find prevention strategies in the form of non-pharmaceutical interventions (NPIs) or non-pharmaceutical interventions. Discussion: This literature review using PICO and PRISMA techniques in extracting the research data based on inclusion and exclusion criteria of several articles on the Database PubMed, Science Direct, and Wiley Online. The readiness of the Government, both in conducting initial screening (Rapid test), readiness of referral hospitals, limiting areas and activities as well as awareness of citizens in implementing new habit adaptations, namely wearing masks, maintaining distance and washing hands regularly are the keys to preventing the spread of the Covid19 virus. Conclusion: articles search from multiple databases, with filtering 2015-2020 study, found as many as 7 Full-text research articles, in the face of a pandemic, we need the readiness of the government, health and infrastructure support as well as coordination and cooperation among all parties.